Capacidade de absorção e qualidade do emprego no setor de serviços - Jorge, Marco Antonio (2000)
The growth of employment in the tertiary sector - trade and services - has been presented as an historica1trend. For decades this sector has been absorbing the workers who have lost their jobs in other economic branches. Would the tertiary, however, be able to create jobs in the exact amount to absorb a1lthose people? And how about the quality of the generated posts? This work aims to give answers to both questions. Then, a detailed analysis of the tertiary sector can be carried into effect. The first chapter starts by relating the characteristics of a service and its consequences to the product measurement of an activity and of a sector aggregation. The second chapter tries to explain why did services become a growing share of the product and of the employment in the world economy. Five hypothesis are mentioned: high income-elasticity of demand, low work productivity in the tertiary sector, growing intertwin between manufacturing and services, higher demand for collective services and, at last, the role of a social 'cushion' played by the sector. The following chapter examines the Brazilian case and conc1udes that unplanned urbanization and the sharpening of social conflicts have put pressure for an active employment policy undertaken by the state. These factors have caused tertiary employment. to grow, but many immigrants could be forced to perform low qualified functions. So, the last chapter analyses the quality of tertiary work posts in the metropolitan area of São Paulo. There is a trade-off between job creation and its quality. While specialized, health and education services seem to be the most suited to employment policies, because they comprise ofhigh quality posts and have some creation capability, 73% of tertiary employment in the region are located in branches with low qualified jobs. There is something worse: during the period 1995/97, 93% of the created posts were in these branches, which means a dangerous threat to the 'health' of our work market.